Failure to Deliver and Translate—New Insights into RNA Dysregulation in ALS - Coyne, Alyssa N.; Zaepfel, Benjamin L.; Zarnescu, Daniela C. (Frontiers in Cellular Neuroscience, 2017)
Amyotrophic Lateral Sclerosis (ALS) is a progressive and fatal neurodegenerative disease affecting both upper and lower motor neurons. The molecular mechanisms underlying disease pathogenesis remain largely unknown. Multiple genetic loci including genes involved in proteostasis and ribostasis have been linked to ALS providing key insights into the molecular mechanisms underlying disease. In particular, the identification of the RNA binding proteins TDP-43 and FUS as causative factors of ALS resulted in a paradigm shift centered on the study of RNA dysregulation as a major mechanism of disease. With wild-type TDP-43 pathology being found in ~97% of ALS cases and the identification of disease causing mutations within its sequence, TDP-43 has emerged as a prominent player in ALS. More recently, studies of the newly discovered C9orf72 repeat expansion are lending further support to the notion of defects in RNA metabolism as a key factor underlying ALS. RNA binding proteins are involved in all aspects of RNA metabolism ranging from splicing, transcription, transport, storage into RNA/protein granules, and translation. How these processes are affected by disease-associated mutations is just beginning to be understood. Considerable work has gone into the identification of splicing and transcription defects resulting from mutations in RNA binding proteins associated with disease. More recently, defects in RNA transport and translation have been shown to be involved in the pathomechanism of ALS. A central hypothesis in the field is that disease causing mutations lead to the persistence of RNA/protein complexes known as stress granules. Under times of prolonged cellular stress these granules sequester specific mRNAs preventing them from translation, and are thought to evolve into pathological aggregates. Here we will review recent efforts directed at understanding how altered RNA metabolism contributes to ALS pathogenesis.